Implementation Backward Chaining to Detect Damage on the Ignition of Aircraft Cessna - Mulyani, Sri (SENATIK STT Adisutjipto, 2018)
Ignition system is one of system to helps in combustion processes on the Cessna aircraft engine. In Cessna aircraft operations, ignition have been often reported to be damaged. Failure modes related to failure of the aircraft are ignored, not working, unserviceable, broken, and burned. Where analysis of aircraft maintenance has 50 times the problem with the ignition system which is dominated by worn out plugs which is 16 times. So the detection of damage aircraft is very important, Backward Chaining is part of the expert system method, where is this method can be used in detect damage  that occurs on the Cessna aircraft with the Best-First Search technique. Using this method can be reduce flight failure with detect damage aircraft.